2018
DOI: 10.4204/eptcs.267.6
|View full text |Cite
|
Sign up to set email alerts
|

Prototyping "Systems that Explain Themselves" for Education

Abstract: Systems that Explain Themselves" appears a provocative wording, in particular in the context of mathematics education -it is as provocative as the idea of building educational software upon technology from computer theorem proving. In spite of recent success stories like the proofs of the Four Colour Theorem or the Kepler Conjecture, mechanised proof is still considered somewhat esoteric by mainstream mathematics.This paper describes the process of prototyping in the ISAC project from a technical perspective. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…Such adpation is concern of a dialogue-module: by use of pattern-matching on the next step a hint can be given in full or partially (from a formula or a tactic, see the example calculation on p.82), can be a list of options or can be idle (in case of a written exam). Such a dialogue-module is implemented as a stub in ISAC's prototype [22], but several field tests [35,33,34] already clarified a lot of requirements for such a module; realisation shall be in collaboration with experts in educational psychology -which exhibits a great advantage of LI over present principles of educational software: design and development in computer mathematics (writing LI-programs, mechanising deductive knowledge) are strictly separated from design and development of dialogues (extending prototypes like [18] and adopting educational theories).…”
Section: Li's Relevance For Educational Mathematics Softwarementioning
confidence: 99%
See 1 more Smart Citation
“…Such adpation is concern of a dialogue-module: by use of pattern-matching on the next step a hint can be given in full or partially (from a formula or a tactic, see the example calculation on p.82), can be a list of options or can be idle (in case of a written exam). Such a dialogue-module is implemented as a stub in ISAC's prototype [22], but several field tests [35,33,34] already clarified a lot of requirements for such a module; realisation shall be in collaboration with experts in educational psychology -which exhibits a great advantage of LI over present principles of educational software: design and development in computer mathematics (writing LI-programs, mechanising deductive knowledge) are strictly separated from design and development of dialogues (extending prototypes like [18] and adopting educational theories).…”
Section: Li's Relevance For Educational Mathematics Softwarementioning
confidence: 99%
“…LI aims at meeting these requirements for more than a decade, when Peter Lucas 3 shifted his interests from programming languages [24] to education. His specific contribution has been named after him, and now reveals the ingenuity of the original design, when the prototype has been migrated: a proprietary version [22] was migrated to Isabelle's function package [20,21] with surprising little effort.…”
Section: Introductionmentioning
confidence: 99%
“…More and more knowledge mechanised in proof assistants addresses problems from STEM faculties, for instance Networks, Security, Economics or Probability Theory in Isabelle's Archive of Formal Proofs 14 . But the kind of explicit specification addressed in the paper is still missing; so specifications need to be added to existing knowledge -assuming to have knowledge associated with specifications covering all undergraduate mathematics seems not unrealistic; see for instance 15 .…”
Section: Technical Facts and Prospectsmentioning
confidence: 99%
“…Small field tests have been mentioned as successful in §1, but the tests also showed that usability in classroom requires considerable efforts to develop prototypes further to such a stage. A possible approach from the side of educational sciences could be to imagine "systems that explain themselves" announced in [15], somewhat naively from an educational point of view. From the side…”
Section: Conclusion On Cooperation Computer Mathematics -Educational mentioning
confidence: 99%
See 1 more Smart Citation